Financial liberalization and institutional development - Markus Alzer; Ramin Dadasov (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper empirically analyzes the effects of de jure financial openness on institutional quality as captured by indicators on investment risk, corruption level, impartiality of judiciary system as well as the effectiveness of bureaucratic authorities. Using a panel data set of more than 110 countries and a time span from 1984 to 2005, we show that a higher degree of financial openness improves institutional quality in particular by reducing investment risks. We also study the effect of a single liberalization reform on the development of institutional quality. Again, we find evidence for the beneficial impact of financial liberalization with the exception of the level of corruption. We additionally show that if financial liberalization is supported by simultaneous political liberalization, the benign consequences of financial opening for the institutional performance are even larger, while financial deregulation in former socialist countries tends to worsen institutional quality.
Keywords: F02; D72; P48; 330; financial integration; liberalization reform; institutional development; institutional dimensions; Finanzsektor; Deregulierung; Institutioneller Wandel; Investitionsrisiko; Korruption; Rechtsstaat; Bürokratie; Schätzung; Welt; Osteuropa